The child’s “or” construction: it’s all about choice - Ariel, Mira; Arnon, Inbal; Katzir, Nicole; Tal, Shira (Frontiers in Communication, 2024)
Or' is associated, in Gricean approaches, with the readings Inclusive ('at least one, and possibly both, options are true') and Exclusive ('exactly one option is true'). Empirical findings show adults favoring Exclusive readings; but for children, the literature yields puzzling results. Laboratory comprehension tasks suggest children favor Inclusive, but naturalistic evidence suggests children's 'or' productions are overwhelmingly Exclusive. We first identify problems with previous research.is not a child-friendly task. And theoretically, Inclusive and Exclusive are not optimal categories for classifying 'or' readings.To resolve the comprehension-production puzzle, we adopt Ariel and Mauri's richer analytic classification of 'or' constructions, where Inclusive and Exclusive as such are not speaker-intended readings, and there are several, rather than one, 'single-option' (Exclusive) readings. We apply this framework in analyzing the Berman corpus of Hebrew child language; and in designing a new, more ecologically valid, experimental task. Study 1 shows that in child-directed-speech, one specific Exclusive 'or' construction, Choice Immediate (e.g. ↗ Chocolates? Or ↘ jelly beans?), is (i) the single dominant 'or' function addressed to children, (ii) the one 'or' reading children consistently respond appropriately to, and (iii) virtually the only 'or' construction children produce. In Study 2, we present young children with a task involving this familiar 'or' construction.The children respond with adult-like mastery even in the absence of a supporting context. These empirical findings argue for a usage-based account of how children acquire 'or'.